Did The Horizontal Referral Policy in Indonesia Create Cost Savings? - Darmasurya, Aditya; Anindita, Rahma; Ikhda, M Candra (BPJS Kesehatan, 2021)
Background: In Indonesia, the referrals to hospitals by Primary Care Providers (PCPs) is high. In 2018, more than 15 per cent of patients visiting PCPs were referred to hospitals, while the cost for outpatient visits reached 51.2 trillion rupiahs. As of September 2019, Indonesia’s Body of Social Security for Health of Indonesia (BPJS Kesehatan) enacted a horizontal referral policy. PCPs will refer patients to other PCPs with more resourced facilities. Objectives: To assess the impact of horizontal referral on hospital outpatient visits and how cost savings were made. Methods: This study is a non-experimental big-data analysis by observational descriptive method. Results: Data results were classified into two groups in order to separate data analysis affected by external COVID-19 pandemic factors. Group I consisted of data from September to December 2019 and group II consisted of data from January 2020 to October 2020. In data Group I, a total of 8.140 cases were referred horizontally and not referred to hospitals. Referral ratio decreased from 16,50% prior the policy enactment to 15,71% in December 2019. In data Group II, horizontal referral showed an increasing trend from January to October 2020 with 56.875 total cases being referred among primary care providers. Cost savings from September 2019 to October 2020 reached 25.891.347.236 rupiahs. Conclusions: The horizontal referral policy in Indonesia reduced the number of patients referred to hospitals, hence creating cost savings. It proposes collaboration among primary care providers, thus controlling unnecessary referrals to hospitals.